Nippon : (Konkusei- Sha, 1990)
"Nippon, a charted survey of Japan," is an English language version of Nihon Kokusei-Zue which was first published in 1927 by late Tsuneta Yano, "NIPPON" has been enthusiastically received in many foreign countries, not to mention